COMMUNITY COLLEGES AND DISTANCE LEARNING - Kathleen Susan Ives (Online Learning, 2019)
The goal of community colleges is to serve local needs. Community colleges’ low tuition helps keep higher education affordable for a diverse population. Distance learning holds the promise of providing yet another mechanism by which community colleges can bring education to a non-traditional student body. This paper explores the role of distance learning opportunities in community colleges within the context of today’s current environmental scan.